2020
DOI: 10.3390/biom10071027
|View full text |Cite
|
Sign up to set email alerts
|

On the Risks of Phylogeny-Based Strain Prioritization for Drug Discovery: Streptomyces lunaelactis as a Case Study

Abstract: Strain prioritization for drug discovery aims at excluding redundant strains of a collection in order to limit the repetitive identification of the same molecules. In this work, we wanted to estimate what can be unexploited in terms of the amount, diversity, and novelty of compounds if the search is focused on only one single representative strain of a species, taking Streptomyces lunaelactis as a model. For this purpose, we selected 18 S. lunaelactis strains taxonomically clustered with the archetype strain S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 39 publications
0
37
0
Order By: Relevance
“…erythropolis PR4 (), and differences are observed only within the middle section. Even when an identical BGC predisposition between two strains is found, it does not necessarily imply chemical uniformity [108]. Thus, we aimed to expand the middle section analysis of most similar BGCs related to strain H-CA8f comprising strains NCTC 8036, R138, PR4, BG43, YL-1 BH4 and 008 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…erythropolis PR4 (), and differences are observed only within the middle section. Even when an identical BGC predisposition between two strains is found, it does not necessarily imply chemical uniformity [108]. Thus, we aimed to expand the middle section analysis of most similar BGCs related to strain H-CA8f comprising strains NCTC 8036, R138, PR4, BG43, YL-1 BH4 and 008 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This result suggests that strain MUSC 125 is tentatively a different bacterial species from Streptomyces pluripotens MUSC 135 T , and they may exhibit differential bioactive potentials. Streptomyces are generally described as heterogenous, even at the strain level in terms of their metabolic profiles [59,60]. Waksman, et al [59] examined different strains of the Streptomyces griseus and found that only a few were able to produce streptomycin as the major product and this was in addition to producing an antifungal actidione.…”
Section: Discussionmentioning
confidence: 99%
“…The genome mining studies showed that all of the strains are genetically equipped with bioclusters predicted to encode for ‘core secondary’ metabolites, such as albaflavenone/geosmin, ectoines, hopenes, melanin and spore pigments, results in good agreement with those of Ward and Allenby ( 2018 ). In contrast, most of the bioclusters predicted to encode for druggable molecules, notably antibiotics, were discontinuously distributed in the genomes of the strains with many being strain specific, as has been found in recent studies on streptomycetes (Vicente et al 2018 ; Martinet et al 2020 ).…”
Section: Resultsmentioning
confidence: 79%
“…The classification of Streptomyces species is especially challenging given the high number of validly published species ( https://www.bacterio.net.streptomyces.html ), the limited resolution of 16S rRNA gene sequences in their delineation (Labeda et al 2012 , 2017 ) and evidence that the genus is underspeciated (Yamac et al 2011 ; Hamm et al 2017 ). However, multi-locus sequence analyses (MLSA) of concatenated protein-coding house-keeping genes (Ayed et al 2018 ; Kusuma et al 2020 ; Li et al 2020 ; Martinet et al 2020 ) and comparative surveys of whole-genome sequences (Nouioui et al 2018 ) provide invaluable data for the circumscription of novel Streptomyces species. MLSA analyses have revealed a correlation between the delineation of phylogenetic clades and associated phenotypic properties (Rong and Huang 2014 ; Labeda et al 2014 ), as exemplified by the assignment of streptomycetes with spiral chains of rugose ornamented spores to a well supported taxon (Labeda et al 2017 ), known as the Streptomyces violaceusniger clade (Sembiring et al 2000 ; Kumar and Goodfellow 2008 , 2010 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation